Completion of probabilistic normed spaces - Bernardo Lafuerza Guillén; José Antonio Rodríguez Lallena; Carlo Sempi (International Journal of Mathematics and Mathematical Sciences)
We prove that every probabilistic normed space, either according to the original definition given by erstnev, or according to the recent one introduced by Alsina, Schweizer and Sklar, has a completion.